Endophytic fungi as potential biocontrol agents of Phytophthora palmivora in the cocoa plant - AGNES VIRGINIA SIMAMORA; MAYAVIRA VERONICA HAHULY; JULINDA BD Henuk (Society for Indonesian Biodiversity, 2021)
Abstract. Simamora AV, Hahuly MV, Henuk JBD. 2021. Endophytic fungi as potential biocontrol agents of Phytophthora palmivora in the cocoa plant. Biodiversitas 22: 2601-2609. In Indonesia, the cocoa tree is one of the essential cultivation crops for farmers. Despite the importance of cocoa cultivation in Indonesia's economy, the productivity of this crop has declined. Cocoa black pod disease caused by Phytophthora palmivora (Butl.) is one of the most severe diseases affecting this crop worldwide, with average annual losses above 40%. Instead of using manufactured chemicals, biological control is an effective and eco-friendly alternative control measure against plant pathogens. This work aimed to assess the potential of endophytic fungi isolated from healthy cocoa pods to control Phytophthora palmivora in vitro and in vivo. Endophytic fungal isolates were classified based on the morphological characteristics of their cultures and reproductive structures. All isolates found were tested to inhibit P. palmivora in the dual culture method, and the best 10 isolates were continued for detached pod assay. Then, the best five isolates (Aspergillus4, Aspergillus5, Aspergillus6, Fusarium6, Ramichloridium sp.) were evaluated for their capability to reduce P. palmivora in cocoa seedlings and in the field plants. Aspergillus, Fusarium, and Ramichloridium showed maximum activity against P. palmivora in dual culture, pod, and seedling assays. Nevertheless, when all these five isolates were applied in the field, they did not suppress the disease development.